Rosin: Recent advances and potential applications in novel drug delivery system. (March 2016) - Yadav, Bhupendra Kumar; Gidwani, Bina; Vyas, Amber
Gum exudates are among the oldest natural polymer. Natural gums have remained one of the major areas of interest for the researchers for their applicability in the drug delivery system because of their wide availability, inexpensiveness and availability in a variety of structures with varied properties. They can be easily modified chemically, biochemically and are highly stable, safe, non-toxic, gel forming and in addition are biodegradable. Rosin is one of the natural gums obtained as resinous constituent of the oleoresin exuded by various species of pine, mostly conifers. Rosin consists primarily of abietic- and pimaric-type resin acids (or rosin acids) with characteristic hydrophobic hydrophenanthrene rings which impart them excellent film-forming properties. Rosin and its derivatives are biopolymers that are increasingly used for their pharmaceutical applications. In the pharmaceutical field, it has been investigated for film-forming and coating properties, microencapsulation and as a matrix material in the tablets for sustained and controlled drug release. This article reviews the literature on rosin and its derivative and describes the varied applications of the rosin and their future exploitation in novel drug delivery systems.